Separation of aromatic from aliphatic by using [EIM][ETSO4] ionic liquid - Che Ahmad Arif, Che Mud (2013)
The separation of aromatic from the aliphatic hydrocarbon mixtures are very challenging since these hydrocarbons have boiling point in a close range and several combination form an azeotrope. Toluene and n-heptane are known to have a very close boiling point, thus difficult to separate by fractionation with distillation. The present studies focusing on separating toluene from n-heptane using 3-ethylimidazolium-ethylsulfate [EIM][EtSO4]. From the analysis of data by using the FTIR and HPLC, the functional group of ionic liquid can be determined as amine group and for the analyzing the data for the extraction, the removal of the toluene from the mixture shows the positive results where the toluene was separated from the aromatic/aliphatic mixtures increases and it depends on the amount or percentages of the volume ratios of the toluene compound in the mixtures. From the results of stirring, it shows that the distribution coefficient of toluene was decreasing with the increasing of the removal of the toluene from the toluene/n-heptane and the selectivities at the temperature 30°C was increasing with decreasing toluene content in the feed.